Distance measurement using frequency scanning interferometry with mode-hoped laser. (June 2016) - Medhat, M.; Sobee, M.; Hussein, H.M.; Terra, O.
Abstract: In this paper, frequency scanning interferometry is implemented to measure distances up to 5 m absolutely. The setup consists of a Michelson interferometer, an external cavity tunable diode laser, and an ultra-low expansion (ULE) Fabry-Pérot (FP) cavity to measure the frequency scanning range. The distance is measured by acquiring simultaneously the interference fringes from, the Michelson and the FP interferometers, while scanning the laser frequency. An online fringe processing technique is developed to calculate the distance from the fringe ratio while removing the parts result from the laser mode-hops without significantly affecting the measurement accuracy. This fringe processing method enables accurate distance measurements up to 5 m with measurements repeatability ±3.9×10 −6 L. An accurate translation stage is used to find the FP cavity free-spectral-range and therefore allow accurate measurement. Finally, the setup is applied for the short distance calibration of a laser distance meter (LDM). Highlights: A tunable laser and an interferometer are used to measure absolute distance. An ultra-low expansion Fabry-Pérot cavity (FP) is used as a frequency reference. A program is developed to enable distance measurement with mode-hops in laser. Distances up to 5 m are measured absolutely with repeatability of ±3.9×10 −6 L. The setup is used to calibrate a Laser distance meter (LDM) over short distances.